2009
DOI: 10.1542/peds.2008-1118
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Physical Activity at Age 13 Years as Predictors of Cardiovascular Disease Risk Factors at Ages 15, 25, 33, and 40 Years: Extended Follow-up of the Oslo Youth Study

Abstract: Although childhood physical fitness seems to reveal some inverse associations with obesity and blood pressure in early adulthood, these effects diminished markedly into middle age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 41 publications
(33 reference statements)
7
67
0
2
Order By: Relevance
“…Further, in accordance with our results other studies have shown that PF at baseline was inverse and significantly associated with adiposity (BMI and skinfolds), as well as other CVD risk factors (24). Besides, a study showed that low-fit children were more likely to be BMI gainers than those classified as fit at baseline (25).…”
Section: Discussionsupporting
confidence: 92%
“…Further, in accordance with our results other studies have shown that PF at baseline was inverse and significantly associated with adiposity (BMI and skinfolds), as well as other CVD risk factors (24). Besides, a study showed that low-fit children were more likely to be BMI gainers than those classified as fit at baseline (25).…”
Section: Discussionsupporting
confidence: 92%
“…The lack of association between PA and blood pressure in our study is in agreement with 231 previous observational studies (28,35), but contradicts randomized controlled trials (36).…”
supporting
confidence: 91%
“…Because of the fact that the progression of cardiovascular diseases has begun from childhood to adulthood, the risks shouldn't be ignored and the preventive precautions should be taken on time (Aires et al, 2011). The cardiovascular diseases depending upon the decrease in the physical activity level and the spread of sedentary lifestyle have showed increased with the adulthood period (Kvaavik et al, 2009). In this study, it has been thought that the evaluation of physical fitness and physical activity levels of adolescents on time and the preventive precautions have been helpful to prevent the possible diseases.…”
Section: Introductionmentioning
confidence: 99%